Cultural rhythmics : applied anthropology and global development from Latin America - Iparraguirre, Gonzalo (Emerald Publishing Limited, 2022)
Presenting an anthropological tool for decision makers and academics who deal with the well-known limitations of linear models of development, Cultural Rhythmics proposes future design strategies useful for business, community leaders, political decision-makers and scientists from all over the world. Framed in the field of applied anthropology and development studies with an action-research pragmatic perspective, Iparraguirre analyses four study cases, calling attention to a specific set of rhythms of life and imaginaries. Introducing cultural rhythmics as a new method to study temporality, spatiality, and rhythms of daily life simultaneously rather than as separate elements, this pioneering ethnographic and interpretative study combines over fifteen years of fieldwork in public sector management of development programs with a symbolic analysis of cultural imaginaries and rhythms of life. Analyzing the symbolic dimension of development in Argentina, Cultural Rhythmics deploys alternative proposals for political and scientific management of these processes in Latin America. Beyond an innovative analysis of the cases presented, Iparraguirre' s rhythmics perspective can be extrapolated to the practices of development and agendas design in other territories of Argentina, Latin America and the Global South. A must-read for development scholars interested in a colonial matrix of thought, Cultural Rhythmics delves into the imaginaries of development and their correlated governance practices applicable in Latin America and beyond.
Keywords: Applied anthropology -- Argentina.; Rhythm -- Social aspects -- Argentina.; Time -- Social aspects -- Argentina.; Economic development -- Social aspects -- Argentina.; Social Science -- Anthropology -- General.; Anthropology.; elektronické knihy; electronic books